Control and Observer Design for Nonlinear Finite and Infinite Dimensional Systems - Meurer, Thomas; Graichen, Knut.; Gilles, Ernst-Dieter.; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg : Imprint: Springer, 2005)
This volume presents a well balanced combination of state-of-the-art theoretical results in the field of nonlinear controller and observer design, combined with industrial applications stemming from mechatronics, electrical, (bio–) chemical engineering, and fluid dynamics. The unique combination of results of finite as well as infinite–dimensional systems makes this book a remarkable contribution addressing postgraduates, researchers, and engineers both at universities and in industry. The contributions to this book were presented at the Symposium on Nonlinear Control and Observer Design: From Theory to Applications (SYNCOD), held September 15–16, 2005, at the University of Stuttgart, Germany. The conference and this book are dedicated to the 65th birthday of Prof. Dr.–Ing. Dr.h.c. Michael Zeitz to honor his life – long research and contributions on the fields of nonlinear control and observer design.
From the contents Observers as Internal Models for Remote Tracking via Encoded Information -- Extended Luenberger Observer for Nonuniformly Observable Nonlinear Systems -- Approximate Observer Error Linearization by Dissipativity Methods -- On Invariant Observers -- Remarks on Moving Horizon State Estimation with Guaranteed Convergence -- Least Squares Smoothing of Nonlinear Systems -- State Estimation of a Molten Carbonate Fuel Cell by an Extended Kalman Filter -- Bioprocess State Estimation: Some Classical and Less Classical Approaches -- Convergent Systems: Analysis and Synthesis -- Smooth and Analytic Normal Forms: A Special Class of Strict Feedforward Forms -- Constructive Nonlinear Dynamics – Foundations and Application to Robust Nonlinear Control -- Optimal Control of Piecewise Affine Systems: A Dynamic Programming Approach -- Hierarchical Hybrid Control Synthesis and its Application to a Multiproduct Batch Plant -- Closed-Loop Fault-Tolerant Control for Uncertain Nonlinear Systems.
Keywords: Control engineering; Robotics; Mechatronics; Vibration; Dynamical systems; Dynamics; System theory; Statistical physics; Control, Robotics, Mechatronics; Vibration, Dynamical Systems, Control; Systems Theory, Control; Complex Systems; Statistical Physics and Dynamical Systems